2020
DOI: 10.1016/j.fuel.2020.118263
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of morphology, nanostructure, and oxidation reaction of soot particulates from CI engines with dimethoxymethane–diesel blends under different loads and speeds

Abstract: Dimethoxymethane (DMM)-diesel blended fuels can simultaneously reduce exhaust emissions of soot and nitrogen oxide (NO X ); several studies have been conducted in this regard. However, the influence of additive DMM on the production of inception and precursors of particulates, especially the relation between oxidation, morphology, and the nanostructure of soot particles has not been extensively investigated. In this study, a transmission electron microscope (TEM) and a thermogravimetric analyzer are introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, there are not many studies on the morphology of fuel alternatives. Qian et al 50 compared Dimethoxymethane (DMM) – diesel blends to diesel at medium and high load conditions in a four cylinder CI engine. Both fuels had similar CN, density and heating value.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are not many studies on the morphology of fuel alternatives. Qian et al 50 compared Dimethoxymethane (DMM) – diesel blends to diesel at medium and high load conditions in a four cylinder CI engine. Both fuels had similar CN, density and heating value.…”
Section: Resultsmentioning
confidence: 99%
“…The internal structure of primary particles can be classified into: (a) purely turbostratic structures; (b) fullerenoid (onion-shaped) structures; (c) turbostratic structures with non-aligned basal planes; and (d) shell-core structures with multiple spherical nuclei oriented concentrically, making up the "outer core" with randomly oriented layers (Figures 3 and 4) [36,47]. Several studies have also reported the ability of particulates to exhibit certain shapes and form chain-like or grain-like structures (e.g., soot from diesel exhaust) [36,48,49]. [51] with the permission of The Journal of Geophysical Research; ref.…”
Section: Particle Morphology As a Modular Of Pm Toxicitymentioning
confidence: 99%
“…The DMM addition leads to a higher degree of graphitization in comparison to D100. Increments of the loading and speed result in an increment of the fringe length with a decrement of the adjacent layer plane distance . Yang et al studied the structure of particulate matter liberated from the different mixtures of diesel and oxygenated fuel poly­(oxymethylene dimethyl ethers) (PODEn) .…”
Section: Formation Of Pollutant Sootmentioning
confidence: 99%